(untitled) (Journal of EAHIL, 2016)
Our role, as librarians and information specialists, must be viewed as relevant and important to stakeholders. Yet key services traditionally associated with libraries now appear to be easily available elsewhere and people often underestimate what we do. We can help redefine these perceptions by changing the way we communicate. Value propositions are simple, yet compelling, messages that summarise the benefits stakeholders will obtain by using our services and resources. These statements are written for a specific audience, based on what they value and what we offer that is special and unique. This article provides the tools to create your own value proposition statements; so that you may articulate your true value in a way that matters, to those that matter.